Cinemeducation in medicine: a mixed methods study on students’ motivations and benefits - Mike Rueb; Matthias Siebeck; Eva A. Rehfuess; Lisa M. Pfadenhauer (BMC Medical Education, 2022)
Abstract Background Cinemeducation courses are used to supplement more standard teaching formats at medical schools and tend to emphasise biopsychosocial aspects of health. The purpose of this paper is to explore why medical students attend the cinemeducation course M23 Cinema (M23C) at LMU Munich and whether a film screening with a subsequent expert and peer discussion benefits their studies and their future careers as medical doctors. Methods An exploratory sequential mixed methods study design was used. Qualitative research, i.e. three focus groups, four expert interviews, one group interview and one narrative interview, was conducted to inform a subsequent quantitative survey. Qualitative data was analysed using qualitative content analysis and quantitative data was analysed descriptively. The findings were integrated using the “following a thread” protocol. Results In total, 28 people were interviewed and 503 participants responded to the survey distributed at seven M23C screenings. Participants perceive the M23C as informal teaching where they learn about perspectives on certain health topics through the combination of film and discussion while spending time with peers. The reasons for and reported benefits of participation varied with educational background, participation frequency and gender. On average, participants gave 5.7 reasons for attending the M23C. The main reasons for participating were the film, the topic and the ability to discuss these afterwards as well as to spend an evening with peers. Attending the M23C was reported to support the students’ memory with regards to certain topics addressed in the M23C when the issues resurface at a later stage, such as during university courses, in the hospital, or in their private life. Conclusions The M23C is characterised by its unique combination of film and discussion that encourages participants to reflect upon their opinions, perspectives and experiences. Participating in the M23C amplified the understanding of biopsychosocial aspects of health and illness in students. Thus, cinemeducative approaches such as the M23C may contribute to enabling health professionals to develop and apply humane, empathetic and relational skills.